POLITIK PENDIDIKAN ISLAM DI ERA DIGITAL: PELUANG DAN TANTANGAN - gustina, zapia; Qolbi Khoiri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The development of this technology provides overall changes that connect every aspect of life, for example in the field of education. By experiencing the development of this technology, it is used as an opportunity to provide effective learning improvements, by providing a breadth of education, and giving rise to new ideas for implementing learning methods. With digitalization, it has an impact on the gap in the digital world, incorrect information and the existence of patterns that are changed due to communication between educators and students. The method used is using library research by analyzing the possible opportunities and obstacles that occur in the digitalization of Islamic education politics. Research conducted by implementing technology in the field of Islamic education can provide increased access and quality of learning. For this reason, a correct way is needed to overcome various obstacles, for example, the lack of digital learning and the risk of technological dependence. Therefore, regulations are needed that emphasize expertise in the digital world for education workers so that there is support for the development of Islamic education in the digital era.